HIGH CONCENTRATION OF 2, 4-D TREATMENT MAY NOT RESULT IN MANTLED VARIATION DURING CALLUS INDUCTION OF OIL PALM - D. Zhang; Y. M. Htwe; Z. Zhao; L. O. Ihase; A. Kareem; P. Shi; Y. Wang; 2 (Journal of Animal and Plant Sciences, 2022)
Mantled is a kind of fruit abnormality in oil palm and can cause serious yield loss of palm oil. It was reported that mantled phenotype could be resulted from the application of plant growth regulators (e.g. 2, 4-D) during tissue culture. However, the effect of 2, 4-D treatment on the development of mantled variation is still very limited. In this study, based on our present oil palm tissue culture system, the inflorescence explants were treated with different concentrations of 2,4-D at callus induction stage to induce mantled. Along with a known mantled sample as control, all 2,4-D treated samples were detected with an available DNA marker (kDEF1) for mantled identification, the expression of EgDEF1 transcripts (kDEF1 and tDEF1) and the accumulation of mantled related metabolites (deoxycytidine) were then analyzed using transcriptomics and metabolomics analysis. Detection of mantled by kDEF1 marker showed that kDEF1 was detected only in control (mantled) sample whereas none was found in 2,4-D treated samples. Furthermore, transcriptome analysis confirmed that kDEF1 transcript was not presented at all in 2,4-D treated samples. In contrast with earlier reports in mantled samples, tDEF1 was down-regulated and the accumulation of deoxycytidine was increased during callus induction. Therefore, the mantled variation was not identified at DNA, RNA and metabolite levels in 2,4-D treated samples, suggesting that high concentration of 2,4-D may not result in mantled variation during callus induction. However, similar research at embryogenesis stage could be till needed to explore more possibilities.
Keywords: Mantled; 2; 4-D; EgDEF1 transcripts; kDEF1; Deoxycytidine